The Late Bronze Age Hoard of Kaleburnu/Galinoporni on Cyprus - Bartelheim, Martin; Kizilduman, Buelent; Muller, Uwe; Pernicka, Ernst; Tekel, Hasan (Acad Sciences Czech Rep, Inst Archaeology, 2008)
On the hill Kral Tepesi/Vasili (Kings Mountain) close to Kaleburnu/Galinoporni on the Karpaz peninsula in the north-eastern part of Cyprus a Late Bronze Age hoard with 26 bronze objects consisting of 16 vessels, three offering stands and 7 tools was found in 2004. The closest parallels to the stands and to some of the vessels were found in some of the most prominent sites in Cyprus and on the nearby Levantine coast (Ugarit, Megiddo, Beth Shan, cave Jatt). The find threw attention on a settlement unknown until then. Regarding the composition of the hoard, especially the presence of the offering stands, the settlement on the hill served not only as a political and economical centre but had probably also the function as a centre for cult and ritual of the region. The excellent quality of the bronze objects and its extraordinarily favourable strategic position point towards an important trade centre. Obviously it had great importance for maritime traffic in the Eastern Mediterranean and stood in close connection with the high and mighty of its time.
Keywords: Cyprus; Late Bronze Age; hoard; bronzes; trade centre